Merci de m'aider à résoudre en mettant le déroulé des opérations pour que je puisse comprendre le résultat

A= 2 (3a + 4) - 4 (2a - 3)

B= (3a - 5) - 2 (1 - 2a) + 3 (-a - 4)

3 (x - 7) + 4 (x + 2) = 5 (2x - 1) -2 (1 - x)

2x -4 = -2

3

1

Réponses

Meilleure réponse !
2013-04-07T13:42:48+02:00

A = 2(3a + 4) - 4(2a - 3)

A = 6a + 8 - 8a + 12

A = -2a + 20

 

B = (3a - 5) - 2(1 - 2a) + 3(-a - 4)

B = 3a - 5 - 2 + 4a - 3a - 12

B = 4a - 19

 

3(x - 7) + 4(x + 2) = 5(2x - 1) - 2(1 - x)

3x - 7 + 4x + 8      = 10x - 5 - 2 + x

7x + 1 - 11x          = 11x - 7 - 11x

-4x + 1 - 1             = -7 - 1

-4x / -4                   = -8 / -4

x                             = 2

 

2x - 4 = -2

   3

2x - 4  *3 = -2

    3

2x - 4 + 4 = - 2 + 4

2x / 2 = 2 / 2

x = 1